1994
DOI: 10.1161/01.str.25.9.1794
|View full text |Cite
|
Sign up to set email alerts
|

Role of angiogenesis in patients with cerebral ischemic stroke.

Abstract: Background and Purpose Stroke is one of the most common causes of mortality and morbidity in the Western world. It results from the occlusion of a cerebral artery followed by severe disturbances in blood supply through microvessels to brain tissue. Despite an extensive literature its pathophysiology is poorly understood, and this has severely impeded the logical development of therapy.Methods Brains were obtained from 10 patients aged 46 to 85 years with survival times of 5 to 92 days after their stroke. Infar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
566
2
12

Year Published

1996
1996
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 780 publications
(599 citation statements)
references
References 23 publications
19
566
2
12
Order By: Relevance
“…In early human studies, the degree of angiogenesis was correlated with the degree of recovery [105]. Angiogenesis and vascular remodeling occur most prominently in peri-infarct tissue [106], although there are changes in vascular structure in cortex contralateral to stroke [107].…”
Section: Tissue Regeneration After Strokementioning
confidence: 99%
“…In early human studies, the degree of angiogenesis was correlated with the degree of recovery [105]. Angiogenesis and vascular remodeling occur most prominently in peri-infarct tissue [106], although there are changes in vascular structure in cortex contralateral to stroke [107].…”
Section: Tissue Regeneration After Strokementioning
confidence: 99%
“…In the early 1990s, Krupinski et al [57] analyzed brain tissues from 10 patients, and found that the number of microvessels, particularly in the penumbra, is significantly increased after cerebral ischemic stroke. The microvessel density correlates with the long-term survival of patients.…”
Section: Angiogenesis After Cerebral Ischemiamentioning
confidence: 99%
“…New vasculature created by angiogenesis at the ischemic border becomes evident at 2 to 4 days after focal ischemia in rats (Hermann and Zechariah, 2009) and correlates with survival in ischemic stroke patients (Krupinski et al, 1994), suggesting that it is a natural recovery process in periinfarct regions. Chronically, hyperperfusion occurs when vasoactive agents such as nitric oxide or adenosine arise from the endothelium or glia (Iadecola and Nedergaard, 2007) and promote CBF increase to serve cellular processes with high energy demands.…”
Section: Delayed Hyperperfusion Coincides With Angiogenesis In the Thmentioning
confidence: 99%